T-Cell Lymphoma with Primary Involvement of Spleen in a Dog - Devika Suresh; Dhanush Krishna, B; Hamza Palekkodan; Pradeep, M; Ajith Jacob George (The Indian Veterinary Journal, 2023)
A dog was presented for postmortem examination revealed enlarged prescapular and mesenteric lymph nodes, splenomegaly with multiple nodules, multiple white focion kidneys and lungs and nodules in mesenteric region. Cytology and histopathology of splenic mass revealed a diffuse population of small to intermediate sized lymphocytes which was also found infiltrated into other visceral organs. Immunohistochemistry of spleen revealed neoplastic lymphocytic cells as T cells. The findings were suggestive of T-cell lymphoma with primary involvement of spleen in a dog.